Correlation of HAS2-associated gene duplications with biological aggressiveness of mast cell tumors in Chinese Shar-Pei dogs - Garner, Alana Pavuk, author; Avery, Anne, advisor; Thamm, Douglas, committee member; Basaraba, Randall, committee member (Colorado State University. Libraries, 2013)
Cutaneous mucinosis in Shar-Pei dogs is the result of excessive dermal hyaluronan, a protein associated with angiogenesis and tumor cell motility in multiple human and canine neoplasms. Cutaneous mucinosis in Shar-Pei has been associated with gene duplications upstream of the hyaluronic acid synthase 2 gene (HAS2). The objective of this study was to evaluate the relationship between HAS2, cutaneous mucinosis, and features of mast cell tumor (MCT) aggressiveness in Shar-Pei dogs. Biopsies of cutaneous MCTs from 149 Shar-Pei and 100 non-Shar-Pei were graded according to two schemes for canine cutaneous MCTs. Biopsies of the Shar-Pei MCTs were also evaluated for degree of cutaneous mucinosis, depth of invasion, and microvessel density (MVD). Shar-Pei and non-Shar-Pei MCTs were evaluated via qPCR for relative copy number of the gene duplication upstream of HAS2. The proportion of grade III tumors was significantly higher in Shar-Pei than the general canine population (p=1.044e-11), with no difference in average age at diagnosis. Shar-Pei biopsies had significantly higher HAS2-associated gene segment duplications than non-Shar-Pei (p=1.128e-11), and copy number was significantly associated with the development of grade III tumors (p=0.0077), mitotic index > or = 7 (p=0.022), and tumoral MVD (p<0.05). Relative copy number was not significantly associated with the degree of cutaneous mucinosis or depth of invasion. Our data suggest a relationship between HAS2 gene duplications and features of MCT aggressiveness in Shar-Pei dogs.
Keywords: mast cell tumor; Shar-Pei dog